2020
DOI: 10.3390/nu12113583
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of an Energy-Restricted Anti-Inflammatory Diet for the Management of Obesity in Younger Adults

Abstract: There is growing evidence of the dietary impact on obesity-induced low-grade chronic inflammation and the associated chronic non-communicable diseases modification. We determined changes in body composition and cardiometabolic and inflammatory status of participants with obesity after 24 weeks of a dietary intervention based on an energy-reduced anti-inflammatory diet and examined the relationship of these changes with changes in the inflammatory potential of the diet. The anthropometric and body composition p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 73 publications
1
26
0
3
Order By: Relevance
“…Heretofore, the role of CMI as a predictor for NAFLD has not been evaluated. Kendel Jovanovic et al [ 50 ] reported that a substantial decrease in CMI was correlated with a significant decrease in total and visceral fat mass. When compared with other indicators, AVI, BAI, and CMI were not identified as significant indicators for NAFLD in previous similar studies [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heretofore, the role of CMI as a predictor for NAFLD has not been evaluated. Kendel Jovanovic et al [ 50 ] reported that a substantial decrease in CMI was correlated with a significant decrease in total and visceral fat mass. When compared with other indicators, AVI, BAI, and CMI were not identified as significant indicators for NAFLD in previous similar studies [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…An anti-inflammatory diet resulted in improvement of fasting glucose, insulin, HOMA-IR, and HBA1c. 117 A previously mentioned intervention study in 45 Brazilian adolescents with obesity 95 that examined the effect of a long-term interdisciplinary therapy found an improvement in DII, fasting glucose, and insulin resistance (HOMA-IR and QUICKI). 95 The subgroup of individuals that decreased their E-DII showed a significantly greater decrease in fasting plasma glucose and insulin sensitivity (QUICKI), 95 although the study did not adjust for reduction in body weight, BMI, and (%) body fat, which occurred as a result of the therapy.…”
Section: Interventional Studiesmentioning
confidence: 96%
“…A randomized controlled intervention trial in 81 Croatian participants with obesity, 117 who underwent a 6-month dietary intervention based on an energy-reduced anti-inflammatory diet or control isocaloric diet, examined the relationship between E-DII and insulin resistance (HOMA-IR) and HBA1c. An anti-inflammatory diet resulted in improvement of fasting glucose, insulin, HOMA-IR, and HBA1c.…”
Section: Interventional Studiesmentioning
confidence: 99%
“…CMI was proposed as a good predictor and discriminator of a central component of metabolic syndrome and diabetes, re ecting both adiposity and blood lipids [26]. Cantero et al reported that the substantial decline of CMI could achieve the largest decrease in TG, LDL-C, total and visceral fat mass [51]. Verma including ABSI and BRI did not integrate into our analysis due to the limitation of their cumbersome formulas and proven poorly diagnostic power for NAFLD compare to WHtR and WHR [12].…”
Section: Discussionmentioning
confidence: 99%